2022
DOI: 10.1073/pnas.2118048119
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcomas are oncogene addicted to the activation of AVIL

Abstract: Significance Rhabdomyosarcoma (RMS) is a common pediatric soft-tissue cancer. There are two main subtypes driven by distinct mechanisms. Currently, there is no targeted therapy for the disease. We found an oncogene AVIL, whose activity is often abnormally up-regulated in RMS. Silencing the gene kills RMS cells and prevents tumor formation in animals; yet, normal control cells are indifferent to the interference. Mechanistically, AVIL activation turns on both oncogene pathways in RMS. These findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In brief, 1 × 10 7 cells were collected and washed two times using PBS. Ribosomes were obtained according to the kit instructions, and then RNA was extracted from ribosomes using TRIzol as previously descried 52 .…”
Section: Methodsmentioning
confidence: 99%
“…In brief, 1 × 10 7 cells were collected and washed two times using PBS. Ribosomes were obtained according to the kit instructions, and then RNA was extracted from ribosomes using TRIzol as previously descried 52 .…”
Section: Methodsmentioning
confidence: 99%
“…These have shown promising effects in some actin-binding targets traditionally considered “undruggable”, such as Rho-GTPases. The ABP AVIL is of particular interest among actin-binding proteins because it is significantly overexpressed in RMS cancer cells while showing low level expression in very few normal cells [ 61 ]. Amplification at the AVIL locus has been shown not only in RMS but in other sarcomas as well, suggesting broader oncogenic properties.…”
Section: Targeting Actin Polymerization and Depolymerizationmentioning
confidence: 99%
“…The AVIL gene is overexpressed in nearly 100% of glioblastomas and was identified as a bona fide oncogene that is crucial for glioblastoma tumorigenesis [ 71 ]. In recent studies, we have shown that AVIL expression is abnormally upregulated in RMS, where silencing this gene results in a dramatic reduction in proliferation and migration, killing cancer cells and preventing tumor formation [ 61 ]. Therefore, AVIL seems to be a viable therapeutic target in glioblastoma and RMS.…”
Section: Advillin Backgroundmentioning
confidence: 99%
See 2 more Smart Citations